PENGARUH STRES KERJA, GAYA KEPEMIIMPINAN, PELATIHAN DAN MOTIVASI TERHADAP PRESTASI KERJA PADA KOPERASI UNIT DESA (KUD)KOTO TINGGI KEC. KOTO BESAR KAB. DHARMASRAYA (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2021)
This study aims to analyze 1) the effect of job stress partially on work performance, 2) the effect of leadership style partially on work performance, 3) the effect of partially training on work performance, 4) the effect of partially motivation on work performance, 5) the effect of work stress, leadership style, training and motivation at the Koto Tinggi Village Unit Cooperative (KUD), Koto Tinggi Kecamatan Koto Besar Kabupaten Dharmasraya. The results of data analysis show that (1) job stress partially has a positive and significant effect on work performance with a coefficient of determination of 0.982, this value is significant because tcount 2.704> ttable 1.69726 and a significant value of 0.011 <0.05; (2) leadership style partially has a positive and significant effect on work performance with the coefficient of determination 0.984, this value is significant because tcount 2.318> ttable 1.69726 and a significant value 0.027 <0.05; (3) partially training has a positive and significant effect on work performance with a coefficient of determination of 0.087, this value is significant because tcount 2.627> ttable 1.69726 and a significant value 0.013 <0.05; (4) motivation partially has a positive and significant effect because the coefficient of determination is 0.929, this value is significant because tcount 2.107> ttable 1.69726 and a significant value of 0.044 <0.05; (5) obtained the results of the f test that work stress, leadership style, training and motivation together have an effect on work performance because Fcount 533.914> Ftable 2.69. The amount of contribution of work stress, leadership style, training and motivation variables simultaneously to work performance is 98.6% and the remaining 1.4% is influenced by other factors not included in this study. Keywoards: Job Stress, Leadership Style, Training and Motivation